2017
DOI: 10.12697/jeful.2017.8.2.07
|View full text |Cite
|
Sign up to set email alerts
|

Partitive subjects in Estonian dialects

Abstract: Abstract. Nominative-partitive alternation in subject marking in Estonian occurs mainly in existentials and related constructions. The paper measures the overall frequency of use of partitive subjects (PS) in Estonian dialects to explore whether differences are found, which can be explained by language contacts. Second, it provides an overview of constructions where PSs occur in Estonian dialects. The data is obtained from the Corpus of Estonian Dialects (12 subdialects, 1517 instances of PS usage). The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
0
8
0
1
Order By: Relevance
“…Note that the partitive-marked subject does not agree with the verb in number. Lindström (2017b) found that partitive subjects occur most frequently with negated verbs, as in (5c), although, as a rule, the alternation between nominative and partitive is taken to express 'bounded' vs 'unbounded' interpretation of the case-marked noun, respectively (see Table 2 above). Thus, effectively, both (5a) and (5b) would also be acceptable with nominative marking instead of partitive.…”
Section: Paradigmatic Case Vs Case Syncretism In Estonianmentioning
confidence: 96%
See 1 more Smart Citation
“…Note that the partitive-marked subject does not agree with the verb in number. Lindström (2017b) found that partitive subjects occur most frequently with negated verbs, as in (5c), although, as a rule, the alternation between nominative and partitive is taken to express 'bounded' vs 'unbounded' interpretation of the case-marked noun, respectively (see Table 2 above). Thus, effectively, both (5a) and (5b) would also be acceptable with nominative marking instead of partitive.…”
Section: Paradigmatic Case Vs Case Syncretism In Estonianmentioning
confidence: 96%
“…In Table 2, 'semantic effect' refers to the interpretation of a case-marked noun as bounded or unbounded; this is explained below. The subject function can be indicated by nominative or partitive (Erelt, Metslang & Plado 2017;Lindström 2017b); nominative subjects occur in examples ( 1)-( 4), and partitive subjects are shown in (5a-b). Note that the partitive-marked subject does not agree with the verb in number.…”
Section: Paradigmatic Case Vs Case Syncretism In Estonianmentioning
confidence: 99%
“…The vast majority of subjects are in nominative, which is morphologically unmarked. However, differential subject marking occurs between nominative and partitive in existential clauses, where partitive seems to indicate reduced transitivity and less agentive subjects (Lindström 2017). In addition, some Experiencers occur in allative or adessive, while some verbs (e.g.…”
Section: Canonical Argumentsmentioning
confidence: 99%
“…Viime aikoina kielitieteessä on keskusteltu usein nominatiivi-ja partitiivisubjektin välisestä vaihtelusta. Sitä on tutkittu esimerkiksi typologian (Luraghi & Kittilä 2014) ja murteiden (Lindström 2017) näkökulmista. Slaavilaisissa kielissä, kuten puolassa (Blaszczak 2009) tai venäjässä, kyseinen vaihtelu tapahtuu nominatiivin ja genetiivin välillä, erityisesti kun verbi on kielteisessä muodossa (Blaszczak 2012, Seržant 2014, Partee & Borschev 2008: tämä ilmiö on suhteessa konst ruktioiden eksistentiaalisuuteen.…”
Section: Johdantounclassified